A Temperature Propagation Calculation Method of Slender Energy Pile and Surrounding Soil Based on the Infinite Line Source Model. Issue 7 (October 2021) - Jin, G G; Chen, L; Lin, H L; Wang, M; Liu, Z Z
Abstract: Based on the infinite line source model, the article proposes a temperature propagation calculating method of the energy pile and surrounding soil considering multiple heating-cooling cyclic temperature. The calculated soil temperatures under different distances at 1.3 D, 2.7 D and 4.7 D (D means diameter of the pile) from the pile center were compared with the centrifuge test results, and the relative errors were 8.57 %, 3.11 % and 1.04 % respectively. The results indicated that under the action of a single cycle of temperature, the difference between the highest and the lowest temperature is 10.62 °C at 1.3D from the center of the pile. The temperature fluctuations at 2.7D and 4.7D are relatively flat, and the temperature differences reach 3.75°C and 1.81°C. In addition, the heat transfer rate per linear meter is relatively stable under heating condition, but it decreases with the increase of pile depth under cooling condition. With the increase of time, the heat transfer rate also has the trend of downward. The calculated results of soil temperature under the action of multi-cycle temperature and the measured value of the centrifugal model test have little error, which can provide a reference for engineering applications.